Presidential leadership and national security : the Obama legacy and Trump trajectory - Conley, Richard Steven (New York : Routledge Taylor & Francis Group, 2018)
"This book assesses the foreign policy legacy of the Obama administration through the lens of national security and leadership. Timely, accessible chapters authored by leading scholars of presidential and international politics cover White House-Cabinet relations; Congress and War Powers; challenges including the Iran nuclear deal, ISIS, and the closing of Guantanamo Bay; drone strikes; the New Cold War with Russia; and the ways in which the Obama foreign policy legacy shaped the 2016 presidential election. In particular, the book explores the philosophical basis of counter-terrorism strategy in the Obama administration and traces how precepts differed from the administration of George W. Bush. More generally, the book contributes to an understanding of the distinctive interplay between the formal, constitutional powers of the president and the use of informal, executive powers in the quest for peace and security. Finally, the book surveys the challenges that Donald J. Trump faces in the transition to the new presidential administration" --
Introduction: the national security transition from Obama to Trump / Richard S. Conley -- Rhetoric, public politics, and security / Cigdem V. Sirin and José D. Villalobos -- Terrorism strategy shifts from Bush to Obama / Karen A. Feste -- Military initiatives by President Obama / Louis Fisher -- Obama's national security cabinet: the fight to survive White House micromanagement / Shirley Anne Warshaw -- Obama and Guantanamo: the intractable-and the internal-dilemma / Nancy Kassop -- Attack of the drones: national security, due process, and the constitutionality of unmanned strikes / Jordan Cash and Dave Bridge -- Obama, unilateral diplomacy, and Iran: treaties, executive agreements, and political commitments / Jeffrey S. Peake -- US-Russian relations during the Obama presidency: from reset to a new cold war? / M. Leann Brown -- The clash of civilizations and the clash of candidates: the 2016 election / Richard S. Conley.
2020.
Includes bibliographical references and index.
Keywords: Obama, Barack; Political leadership -- United States; United States -- Foreign relations -- 2009-2017.